Advanced materials in machine design : special topic volume with invited peer reviewed papers only - Muc, Aleksander, editor; Barski, Marek; Kedzioria, P., editor (Durnten-Zurich : Trans Tech Pubn, 2013)
Includes bibliographical references and index